2023
DOI: 10.1172/jci.insight.167490
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling reveals pathogenic role and differentiation trajectory of granzyme K+CD8+ T cells in primary Sjögren’s syndrome

Abstract: Primary Sjogren's syndrome (pSS) is a systemic autoimmune inflammatory disease mainly defined by T cell-dominated destruction of exocrine glands. Currently, CD8 + T cells were closely related to the pathogenesis of pSS. However, the single-cell immune profiling of pSS and molecular signatures of pathogenic CD8 + T cells have not been well elucidated.Our multiomics investigation identified that both T cell and B cell, especially CD8 + T cells, were undergoing significant clonal expansion in pSS patients. TCR cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…To determine the clinical relevance of these highly activated CD8 + T cells, we compared them to CD8 + T cells associated with Sjogren’s Syndrome in human patients 31,32 . In Sjogren’s Syndrome patients, pathogenic resident GzmK + CD8 + T cells expand and correlate with disease severity 32 . Importantly, of 50 genes differentially upregulated in those cytotoxic T cells, 17 are also upregulated in the murine CD8 Activated 3 cluster of interest ( Supplemental Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the clinical relevance of these highly activated CD8 + T cells, we compared them to CD8 + T cells associated with Sjogren’s Syndrome in human patients 31,32 . In Sjogren’s Syndrome patients, pathogenic resident GzmK + CD8 + T cells expand and correlate with disease severity 32 . Importantly, of 50 genes differentially upregulated in those cytotoxic T cells, 17 are also upregulated in the murine CD8 Activated 3 cluster of interest ( Supplemental Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the CD8 + T cells of interest express high levels of GzmK , consistent with highly activated CD8 + T cell populations. A recent study from primary Sjögren’s Syndrome patients found a population of CD8 + T cells with high expression of GzmK that are highly active and cytotoxic 32 . Notably, in this data set, upregulated expression of GzmK correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using scRNA-seq and analyzing PBMCs in a handful of patients with pSS have primarily reported differences in the T cell compartment, whereas the B cells were only briefly considered. 13,[24][25][26] Here, we assigned the individual B cells into 16 cellular states, all present in both patients and controls, but with a shift in the composition of B cell subtypes. The largest difference compared with controls was seen in the SSA/SSB+ patient group.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first large‐scale study in which B cell composition and BCR gene usage have been investigated at the single‐cell level in patients with pSS stratified for SSA/SSB antibodies. Previous studies using scRNA‐seq and analyzing PBMCs in a handful of patients with pSS have primarily reported differences in the T cell compartment, whereas the B cells were only briefly considered 13,24–26 . Here, we assigned the individual B cells into 16 cellular states, all present in both patients and controls, but with a shift in the composition of B cell subtypes.…”
Section: Discussionmentioning
confidence: 99%